Vulnerabilidade à inundação na bacia hidrográfica do Rio Una - PE utilizando análise hierárquica de processo - Silva, Fernanda Cláudia Barboza da (2020)
The mismatch between water resources management and land use planning results in disorderly occupation on river banks compromising the quality of life of society. The Una river basin has a history of flooding, highlighting the great importance of monitoring risk areas, which we intend to VIII ENSUS – Encontro de Sustentabilidade em Projeto – UNISUL – Palhoça – 12 a 14 de maio de 2020 identify in the present study. The flood vulnerability map was developed using the methodology proposed by Saaty (1980) combined with map algebra performed in a geographic information system. In the hierarchical process analysis, the variables that most influenced were slope and hypsometry, followed by land use and, finally, pedology. The results show that the areas most vulnerable to flooding comprised mainly the lower elevation range in the basin and near the river bank. Flood-related problems can be minimized by adopting structural and non-structural measures combined with geoprocessing techniques.